2022
DOI: 10.2478/bhk-2022-0026
|View full text |Cite
|
Sign up to set email alerts
|

Acute caffeine mouth rinse does not affect attention and hand-eye coordination in recreationally active adults

Abstract: Study aim: The purpose of this study was to evaluate the acute effect of different four caffeine mouth rinse intervention (caffeinated coffee, decaffeinated coffee, placebo, control) on attention and hand-eye coordination. Material and methods: Sixty-five healthy, recreationally active female (n = 41) (age 22.89 ± 3.94 years; body mass index 20.87 ± 2.63 kg/m2) and male (n = 24) (age 29.91 ± 12.06 years; body mass index 22.56 ± 2.21 kg/m2) volunteered to participate in this ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…For example, a study observed that consuming caffeine in moderate doses leads to strengthening memory and motor coordination performance [ 35 ]. But a study showed that rinsing the mouth with espresso coffee did not affect the attention and hand-eye coordination of active adults [ 36 ]. Differences in exercise fields and caffeine supplementation dosage may contribute to the heterogeneity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study observed that consuming caffeine in moderate doses leads to strengthening memory and motor coordination performance [ 35 ]. But a study showed that rinsing the mouth with espresso coffee did not affect the attention and hand-eye coordination of active adults [ 36 ]. Differences in exercise fields and caffeine supplementation dosage may contribute to the heterogeneity of the results.…”
Section: Discussionmentioning
confidence: 99%